A new equipment effectiveness and sustainability performance model for palm oil mill - Abdullah, Ilyana (2018)
The worldwide demands for sustainable palm oil products are in the increasing trend due to rising awareness of the palm oil industry impact on environment.Hence,the urgency to develop a sustainability strategy to overcome these issues is imminent.The objectives of this research are to investigate the current practices and performance of manufacturing sustainability in the Malaysian Palm Oil Mill (POM),identify factors affecting equipment effectiveness in the Malaysian POM,develop a model for equipment effectiveness and sustainability performance, and validate the model using data from the Malaysian POM. The research opted for an exploratory study using the survey instrument on Malaysian POM against the 20 elements of sustainability programs and practices,18 elements of regulatory compliance,32 elements of factors affecting equipment effectiveness,and 36 elements of manufacturing sustainability opportunity from equipment effectiveness.Out of 250 questionnaires randomly sent to 426 registered POM in Malaysia,a total of 55 were completed and returned by the surveyed mills.After screening,51 of those completed with useful information were further analysed,representing 11.97% of the population with a response rate of 20.4%.The research developed a new model for measuring equipment effectiveness and sustainability performance.This model hybrid the concept of Overall Equipment Effectiveness (OEE),equipment reliability and Failure Mode and Effect Analysis (FMEA).In appraising the criticality in terms of sustainability impact of equipment failure occurrence,the model ranks the sustainability performance of the failure mode by using the Sustainability Priority Number (SPN), formulated using Analytical Hierarchy Process (AHP) approach.The performance level of the OEE,reliability and SPN resulting scores translated into a five-point rating system.The model has been tested on a POM as the validation approach to demonstrate the feasibility of the model for equipment effectiveness and sustainability performance analysis.The findings emphasis on the fluctuation in the OEE performance depending on the month,suggest that waiting time,breakdown,and preventive maintenance as the key factors affecting equipment effectiveness.Further,reliability performance of the model exhibits an increasing failure rate indicating that the probability of failure occurrence increases over time for the critical equipment (loading ramp,steriliser, thresher,and boiler).The model determines the performance level of 20 functional failure modes of the critical equipment and the results show that the highest SPN ranking for steriliser,signify as the most critical functional failure mode for sustainability impact in the POM.The model is able to analyse equipment effectiveness and sustainability performance in the POM and provide empirical evidence to support the decision making for POM sustainability.This research can be used as an advantage in POM as well as other organisation from different industries to recognise the opportunities of equipment effectiveness in the efforts to enhance the business profile and corporate reputation,and market growth without disregarding the environmental and social impact.